Pengaruh Modal dan Tenaga Kerja terhadap Pendapatan UMKM Kerupuk Ikan SPN Kota Jambi - Habriyanto Habriyanto; Bambang Kurniawan; David Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of working capital and labor on the income of MSME fish cracker SPN Jambi City in a quantitative descriptive of: How are the effects of working capital and labor on the income of fish cracker fish in Jambi City. This research is expected to provide benefits to authors, agencies, and academics related to SPN fish cracker income, as well as a source of information for SPN fish cracker business owners in order to optimize their income. This type of research is quantitative-descriptive, because this research accommodates the form of numbers and data processing using multiple linear regression analysis with the help of the IBM statistics 22 application. The data used is secondary data in the form of time series data from 2018 to 2020 which is obtained from the SPN fish cracker business owner. Based on the results of research that has been done, data obtained from the variables of working capital and labor have a positive and significant effect on income. Based on the test using main component analysis, it shows that the working capital variable has a significant value (0.00 <0.05) with a coefficient value of 0.724. , the labor variable has a significant value (0.755 <0.05) with a coefficient value of .042.